Non-contact specular microscopy in aphakic and pseudophakic dogs - Claudia Emi Nagatsuyu; Priscila Barreto de Abreu; Karina Kamachi Kobashigawa; Luciano Fernandes da Conceição; Adriana Morales; Alexandre Lima de Andrade; Ivan Ricardo Martinez Padua; Bianca da Costa Martins; José Luiz Laus (Ciência Rural, 2014)
Cataract is one of the most common ocular diseases in dogs, and phacoemulsification is considered its treatment of choice. Posterior capsular opacity (PCO) is a frequent complication and may occur weeks or months after the surgery. It is known that intraocular lenses (IOL) used for the correction of post-operative hypermetropia are an adjunctive aid in the prevention of PCOs, mainly the foldable acrylics designs with square and truncated edges. However, IOL placement may result in endothelial cell loss. This study evaluated the morphology and cellularity of the endothelium by non-contact specular microscopy in aphakic and pseudophakic dogs. Endothelial cell density, endothelial cell area, coefficient of variation and hexagonal cells percent were analyzed for each group and between groups. During all evaluation periods, endothelial cell density did not alter in any group. From days 7 to 30, endothelial cell density was higher in pseudophakic dogs. However, values returned to normal and, by the end of the study, no significant difference was observed. Cell area and variation coefficient did not differ in each group or between groups. Hexagonal cells percent significantly reduced after phacoemulsification in both groups. With time, this condition returned to initial values. When both groups were compared, hexagonal cells percent were decreased in the pseudophakic group, immediately after the surgeries.